CRIMINAL LIABILITY AGAINST CHILDREN AS OFFENDERS OF NARCOTICS ABUSE BASED ON THE DECISION OF THE TEBING TINGGI DISTRICT COURT NO. 21/PID.SUS-ANAK/2018/PN.TBT - Lidya Gultom, Syafrudin Kalo, Mahmud Mulyadi, M. Ekaputra (Res Nullius Law Journal, 2021)
The development of narcotics abuse is increasingly increasing. The government has issued regulations governing the handling of children as perpetrators of criminal acts of narcotics abuse, namely Law No. 35 of 2009 concerning Narcotics and Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. This study will examine and analyze the Tebing Tinggi District Court Decision No. 21/Pid.Sus-Anak/2018/PN.TBT., Which has been decided by the judge for action against the child perpetrator of the crime of narcotics abuse, even though in the case diversion can be carried out, but not done. The problems in this study, namely: the criminal responsibility of child offenders of criminal offenses of narcotics abuse based on the Narcotics Law and the Child Criminal Justice System Law; analysis of decisions used as examples of cases in this study. This research is a descriptive normative legal research analysis. The data used are secondary data and empirical data. Furthermore, analyzed using qualitative analysis methods. The results showed that: First, the criminal act of narcotics crime based on the Narcotics Law and the Juvenile Criminal Justice System Law in both laws have narcotics crime; Second, Tebing Tinggi District Court Decision No. 21/Pid.Sus-Anak/2018/PN.TBT., Diversion was not attempted, which the Law Enforcement Officials, investigators, public prosecutors, and judges can seek diversion based on Article 7 of the Juvenile Criminal Justice System Law to avoid children from the judicial process, but not carried out.